Bibliometric Analysis of Character Education in Senior High School Indonesian Textbooks Based on the Merdeka Curriculum - Huda, Muhammad Binur; Suyitno, Imam; Pratiwi, Yuni; Roekhan, Roekhan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study aims to understand the publication trend and research contribution related to character education in Indonesian high school textbooks based on the Merdeka Curriculum from 2015 to 2024. Character education is crucial for student development, and textbooks play a central role. Using bibliometric analysis, the study identified 428 publications from Google Scholar and Scopus, including journal articles, proceedings, reviews, and books. Journal articles dominated with 363 publications, followed by 30 proceedings, 32 books, and three reviews. The study focused on the number of publications and the issues underlying the keyword emergence. While 2023 had the highest number of publications (75), 2018 saw the highest citations (890) and h-index (14), indicating significant influence. The highly cited study